Fiqh Penyelenggaraan Jenazah dalam Rangka Meningkatkan Sumber Daya Warga Binaan Penjara di Lapas Kelas IIA Tembilahan Indragiri Hilir Riau - Junaidi, Junaidi; Afrizal , Jon; Sukanti, Nadia Deby; Nur , Syamsiah; Rahayu, Marlisa (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
The focus of this research is how the Fiqh of funeral arrangements can be a way to increase the knowledge of the inmates of class IIA Tembilahan prison. This is intended so that the inmates have sufficient provision of religious knowledge, and it will be useful when they are free and mingle with the society to which they are returned. This research is an Islamic law research with an interdisciplinary study of Fiqh. This research uses a large study of sharia science and sciences related to Islamic guidance, especially the practice of worship and other social sciences from a societal perspective. The findings from this study are that the enthusiasm and seriousness of the participants in listening to explanations about the Fiqh of organizing a funeral needs to be appreciated. For the participants, not much knowledge about the Fiqh of organizing the funeral was conveyed by the instructors, so that practice and theory were not always well understood. So with this activity, that opinion changed and the understanding of the Fiqh of organizing the funeral became one of the ways to increase the religious knowledge of the inmates of the prison. As a follow-up, it is necessary to have complete media so that the activity process can be maximized bearing in mind that the participants are seen as relatively large.